Red Ginseng Root Extract Mixed with Torilus Fructus and Corni Fructus Improves Facial Wrinkles and Increases Type I Procollagen Synthesis in Human Skin: A Randomized, Double-Blind, Placebo-Controlled Study - Cho, Soyun; Won, Chong-Hyun; Lee, Dong Hun; Lee, Min-Jung; Lee, Serah; So, Seung-Ho; Lee, Seong-Kye; Koo, Bon-Suk; Kim, Na-Mi; Chung, Jin Ho (Journal of medicinal food, 2009)
Red ginseng contains many bioactive constituents, including various ginsenosides that are believed to have antioxidant, immunostimulatory, and anti-aging activities. Yet, no controlled human study has explored its effects on photoaged skin. This study determined whether long-term intake of a red ginseng extract-containing Torilus fructus and Corni fructus mixture reduces facial wrinkles and increases collagen synthesis in human skin. Healthy female volunteers over 40 years of age were randomized in a double-blind fashion to receive either red ginseng extract-containing herbal mixture at 3 g/day or placebo for 24 weeks. Facial wrinkles, elasticity, epidermal water content, erythema, and pigmentation were measured objectively. Facial skin samples were taken before and after treatment, and real-time polymerase chain reaction and immunohistochemical analyses were undertaken for expression of type I procollagen, matrix metalloproteinase (MMP)-9, and fibrillin-1, which are wrinkle-related biochemical markers. A total of 82 subjects completed the study. Facial wrinkles were significantly improved, type I procollagen gene and protein expression was increased, MMP-9 gene induction was prevented, and fibrillin-1 fiber length was elongated only in the treatment group. No changes were seen in the facial elasticity, epidermal water content, facial erythema and pigmentation, and epidermal thickness in either group. Thus a red ginseng extract-containing Torilus fructus and Corni fructus mixture improves facial wrinkles, a clinical sign of photoaging, and this improvement is associated with biochemical and histological evidence of increased collagen synthesis in the dermis. These results substantiate the alleged beneficial effects of red ginseng on photoaging and support its use as an effective "beauty food."